Improving decisions under uncertainty 2 - Payne, John W. (Henry Stewart Talks, 2011)
Confirmation and overconfidence biases, Typical calibration curve for being right, The gap between confidence and accuracy, Tools for improving assessments of uncertainty, Properties of human preferences, Prospect theory: value properties, Weighting of values by probabilities, "Formal" risk analysis process, Dealing with "risky" options, Risk management strategies